Cover Picture: Enhanced Electrocaloric Effect in Pre‐stressed Ferroelectric Materials (Energy Technol. 2/2015). Issue 2 (February 2015) - Chauhan, Aditya; Patel, Satyanarayan; Vaish, Rahul
<x xml:space="preserve">Abstract</x> Production under stress: The cover picture demonstrates the solid‐state cooling application and mechanism in ferroelectric materials. Refrigeration and air‐conditioning systems employing solid‐state ferroelectric technology are potential candidates for replacing conventional vapor‐compression systems for low‐ to medium‐load cooling requirements. Such systems offer potential advantage of high efficiency, embedded cooling, and environmental‐friendly operation while minimizing the use of harmful coolants. Rahul Vaish and colleagues at the Indian Institute of Technology Mandi have explored the possibility of enhancing the cooling capacity of ferroelectric materials by the application of compressive pre‐stresses, ultimately obtaining an improvement of nearly 80% in the adiabatic temperature change (as described in the Full Paper on page 177). The backdrop image is a photograph of the campus of Indian Institute of Technology Mandi where the research was performed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>